Relasi Agama dan Negara Perspektif Analisis Ushul Fikih: Pola Kontrol Terhadap Kemashlahatan Sosial Antara Agama dan Negara - A. Faiqil Faqih, Faqih (Mahad Aly Al Fithrah, 2022)
Religious-state conflicts coloured the journey of this nation since begun the establishment of the Republic Indonesia (since independence), starting from conflicts about formulation of Jakarta Charter to conflicts that have occurred recently. The conflict that occurred with regard to the Jakarta Charter was nothing more than a conflict about the basic formulation of the state, whether the State of Pancasila or the Islamic State. Then continued with conflicts related to the PKI, a conflict of faith movements involving clashes among the abangan’s community, students and the military. Not only that, there are many others about religious-state conflicts. This article wants to understand comprehensively about the state and religion (Islam), in order can read the relationship beetwen synergize religion with the state. The following synergence of religion and state will be formulated based on the dialectical formulation between wa>zi’ di>niy (regulator and supervisor religion: religious control) and w?zi’ sulta>niy (regulator and supervisor government: government control) based on the study of Jurisprudence Proposal. This research results that religion (it means, Islam) and the state have common ground in an effort to realize the social benefit of society. Islam is a control for Muslims to realize benefits because Islam believed by the true religion by Muslims. The state became control to realize benefits because the state has the authority to regulate and make policies for all its people. In the role of being a control for the benefit, there is no superior between religion and the state.